Customer intention on service robots’ technology in the hospitality industry: a study in Kuala Lumpur / Dylan Orson Chius ... [et al.] - Chius, Dylan Orson; Abd Razak, Nasreen Natasha; Ismail, Sara Nabila; Azeman, innin Sofea (Universiti Teknologi MARA, Terengganu, 2024)
Though frequently discussed, technology is often misunderstood beyond its basic forms, such as machinery and electronic devices. In the context of rapid advancements in digital tools and frontier technologies like artificial intelligence (AI) and robotics, understanding their impact on various industries is crucial. This study is based on the service robots’ influence on customer intentions in Kuala Lumpur, Malaysia. This research used a quantitative approach involving a survey through Google Forms. The survey was also distributed via social media platforms like WhatsApp and Telegram. This study measured customer intention, trust, performance expectancy, and perceived value using a 5-point Likert scale for the survey. Thirty respondents were asked for the pilot study, which helped to ensure clarity and refine the questionnaire. Using SPSS, the reliability test was used as the values of Cronbach’s Alpha are between 0.8 and 0.9. The findings show a relationship between trust and perceived value with customer intention, as mentioned in previous studies that said significant roles in technology adoption. Performance expectancy also showed a relationship with customer intention, though to a lesser extent. This suggests that while Kuala Lumpur residents are receptive to service robots in the hospitality sector, the impact of expected performance is somewhat less influential. This study provides insights into the acceptance of service robots in Malaysia’s hospitality industry. It underscores the need for further research on the evolving role of technology in enhancing service experiences. The results contribute to understanding technology adoption in emerging markets and offer a basis for future studies on technological advancements in hospitality.